A Concise Account of the Chemistry of Valuable Alkyl(methyl)maleic Anhydrides - Deore, Prashant S.; Haval, Kishan P.; Gadre, Smita R.; Argade, Narshinha P. (Synthesis, 2014)
A large number of significant bioactive natural and synthetic alkyl(methyl)maleic anhydrides are known in the contemporary literature. A broad range of suitably functionalized substrates have been tailored to accomplish concise and efficient syntheses of an array of alkyl(methyl)maleic anhydrides employing a variety of elegant synthetic strategies. This review presents a brief literature account of the isolation and activity of these important target compounds with a special emphasis on their synthesis.1 Introduction2 Recent Synthetic Strategies towards the Natural and Unnatural Alkyl(methyl)maleic Anhydrides2.1 Dimethylmaleic Anhydride2.2 Ethyl/hexyl/octyl(methyl)maleic Anhydrides2.3 Chaetomellic Anhydrides A–C2.4 Tyromycin A2.5 Aspergillus Acids A–D2.6 Tautomycin and Tautomycetin2.7 Lindenanolide E, Itaconitin, Graphenone and 2,3-Didehydrotelfairic Anhydride2.8 Synthetic Analogues of Alkyl(methyl)maleic Anhydrides3 Summary
Keywords: dimethylmaleic anhydride; alkyl(methyl)maleic anhydrides; isolation; bioactivity; nucleophilic reactions; total synthesis